2002
DOI: 10.1055/s-0037-1612975
|View full text |Cite
|
Sign up to set email alerts
|

Prospective Study on Soluble Thrombomodulin and von Willebrand Factor and the Risk of Ischemic and Hemorrhagic Stroke

Abstract: SummaryThe aim of the present study was to examine if soluble thrombomodulin (sTM) and von Willebrand factor (VWF) could predict a first-ever ischemic or hemorrhagic stroke.This study was an incident case-referent study from within a population-based cohort in northern Sweden. Up to 1996 about 44,000 subjects had been screened and stroke cases were classified according to the WHO MONICA criteria. A first-ever stroke occurred in 108 cases. A total of 216 controls were selected from the same cohort.This prospect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
19
1

Year Published

2003
2003
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 29 publications
1
19
1
Order By: Relevance
“…The vWF was shown to be predictive of stroke in the Rotterdam and Atherosclerosis Risk in Communities (ARIC) studies, 9,10 but others have reported no independent association between vWF and stroke [11][12][13][14] ; however, many of these studies were based on smaller participant numbers. Our results, generated in a more homogenous population of predominantly white men, provide additional support for an independent association between vWF and stroke that is not explained by inflammation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The vWF was shown to be predictive of stroke in the Rotterdam and Atherosclerosis Risk in Communities (ARIC) studies, 9,10 but others have reported no independent association between vWF and stroke [11][12][13][14] ; however, many of these studies were based on smaller participant numbers. Our results, generated in a more homogenous population of predominantly white men, provide additional support for an independent association between vWF and stroke that is not explained by inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…4 The von Willebrand factor (vWF) is synthesized primarily by vascular endothelial cells and promotes platelet adhesion and aggregation, leading to thrombus formation. 1 Increased levels of vWF in stroke patients have been reported in several case-control studies, [5][6][7][8] but prospective studies have been inconsistent, with some showing a positive relationship 9,10 and others showing no relationship [11][12][13][14] between vWF and stroke risk. Fibrin D-dimer is the primary degradation product of cross-linked fibrin and is a marker of activated coagulation and fibrinolysis.…”
mentioning
confidence: 99%
“…In the multivariate analysis, we found a positive independent association between tPA/PAI-1 complex and ICH and an inverse independent association between sTM and ICH. 4,5 The primary aim of the present prospective study was to test the hypothesis that concentrations of tPA/PAI-1 complex, tPA, PAI-1, sTM, and von Willebrand factor (VWF) were associated with hemorrhagic stroke in a study population without previous stroke, myocardial infarction, or cancer. Furthermore, a secondary objective was to investigate the relationship and possible interactions between tPA/PAI-1 complex, tPA, PAI-1, sTM, VWF, and cardiovascular risk factors and the risk for ICH in this study population.…”
mentioning
confidence: 99%
“…[24][25][26] Although many reports showed decreased platelet adhesion under flow conditions when plasma VWF was genetically deficient or inhibited by antibodies, 10,12,38,39 platelet adhesion and aggregation under flow conditions in the presence of higher concentration of VWF have not received much attention. In the present study, we analyzed platelet adhesion to an immobilized-collagen surface under flow using blood containing an extra amount of VWF, compared with the physiologic amount in normal blood.…”
Section: Discussionmentioning
confidence: 99%
“…[24][25][26] Those reports suggested that high level of FVIII or VWF in blood might have an ability to increase the hemostatic potential in patients with bleeding episodes caused by a defect in blood coagulation or thrombocytopenia. The vasopressin agonist desmopressin (DDAVP) is known to be an inducer of VWF release from endothelial cells and is used to control the bleeding of mild hemophilia and von Willebrand disease (VWD).…”
Section: Introductionmentioning
confidence: 99%